2019
DOI: 10.1111/1759-7714.13131
|View full text |Cite
|
Sign up to set email alerts
|

CircAGFG1 sponges miR‐203 to promote EMT and metastasis of non‐small‐cell lung cancer by upregulating ZNF281 expression

Abstract: The circRNA circAGFG1 is reported to be important in triple‐negative breast cancer progression. However, the mechanism of circAGFG1 in non‐small‐cell lung cancer (NSCLC) remains unknown. In this study, expression of circAGFG1 was determined by real‐time PCR in 20 pairs of NSCLC tissues and adjacent tissues. Next, functional experiments with circAGFG1 were performed in vitro to evaluate the role of circAGFG1 in tumor metastasis and growth. Meanwhile, a dual luciferase reporter assay, RNA pull‐down and RNA immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Several circRNAs have been reported to be aberrantly expressed and associated with the tumorigenesis of lung cancer . Furthermore, emerging evidence suggests that several circRNAs might contribute to the progression of NSCLC . Accruing evidence demonstrates that circRNA antisense to cerebellar degeneration‐related protein 1 transcript (circCDR1as) could promote the development of hepatocellular carcinoma, colorectal cancer and laryngeal squamous cell carcinoma and inhibit the progression of bladder cancer and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several circRNAs have been reported to be aberrantly expressed and associated with the tumorigenesis of lung cancer . Furthermore, emerging evidence suggests that several circRNAs might contribute to the progression of NSCLC . Accruing evidence demonstrates that circRNA antisense to cerebellar degeneration‐related protein 1 transcript (circCDR1as) could promote the development of hepatocellular carcinoma, colorectal cancer and laryngeal squamous cell carcinoma and inhibit the progression of bladder cancer and ovarian cancer .…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, emerging evidence suggests that several circRNAs might contribute to the progression of NSCLC. [8][9][10] Accruing evidence demonstrates that circRNA antisense to cerebellar degeneration-related protein 1 transcript (circCDR1as) could promote the development of hepatocellular carcinoma, colorectal cancer and laryngeal squamous cell carcinoma and inhibit the progression of bladder cancer and ovarian cancer. [11][12][13][14][15] Importantly, a previous study reveals that circCDR1as acts as an oncogene to facilitate the development of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, circRNA-miRNA-mRNA axis might play an important role in cancer-related pathways (25). Huang et al found that circRNA_001946 could promote EMT and metastasis of NSCLC cells via a circAGFG1/miR-203/ZNF281 axis (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study indicated that circRNAs regulated the expression of the target genes via acting as a microRNA sponge (13). Xue et al found that circAGFG1 promoted metastasis in NSCLC cells by sponging miR-203 (14).…”
Section: Introductionmentioning
confidence: 99%
“…[20] It has been shown that circRNA can affect the migration, invasion and EMT in various tumors, including BC. [21][22][23][24][25] Dual luciferase reporter and RIP assay results showed that circPVT1 could sponge miR-140-3p, and that miR-140-3p could target TRPS1. Further, Cytological studies showed that the lower circPVT1 expression can effectively inhibit cell proliferation, migration, invasion, and the EMT in BC cells by targeting TRPS1 via miR-140-3p.…”
Section: Discussionmentioning
confidence: 99%